Hubungan Antara Masa Kerja Dan Durasi Kerja Dengan Keluhan Musculoskeletal Disorders (Msds) Pada Pengrajin Tenun - Diah Puspita Kusuma Adnyani, Ni Putu; Pebruanto, Henry; Ashhabul Kahfi Mathar, Muhammad; Karmila, Dany (Journals of Ners Community, 2023)
Musculoskeletal Disorders (MSDs) or musculoskeletal disorders are disorders characterized by injuries to muscles, tendons, ligaments, nerves, cartilage, bones, or blood vessels in the hands, feet, neck, and back. The World Health Organization (WHO) estimates that the prevalence of MSDs is nearly 60% of all occupational diseases. Most musculoskeletal disorders develop over time. Weaving work is work done by sitting continuously. The study aimed to determine the relationship between a work period and work duration with complaints of musculoskeletal disorders (MSDs) among weaving craftsmen in the tourism area of ​​Dusun Sade, Lombok Tengah. Observational analytic quantitative research with cross-sectional research design. The sampling technique uses total sampling. The research was conducted in Sade Hamlet, Lombok Tengah. The research sample is 76 respondents. The data obtained were analyzed using the Chi-square test. Respondents who had worked > 5 years (long) totaled 74 people (93,4%) who suffered from MSD complaints and the results of the analysis using Chi-square obtained a p-value of 0.00 (p-value <0.05). Respondents who had working duration > 8 hours/day (long) who suffered from MSDs were 68 people (88,2%), the results of the analysis using Chi-square obtained a p-value of 0.00 (p-value <0.05). There is a significant relationship between work duration and MSD complaints and there is a significant relationship between work duration and MSD complaints among weaving craftsmen in Sade Hamlet, Central Lombok Tengah